2009
DOI: 10.1128/aem.00950-09
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Homoserine Lactones Can Induce Virus Production in Lysogenic Bacteria: an Alternative Paradigm for Prophage Induction

Abstract: Prophage typically are induced to a lytic cycle under stressful environmental conditions or when the host's survival is threatened. However, stress-independent, spontaneous induction also occurs in nature and may be cell density dependent, but the in vivo signal(s) that can trigger induction is unknown. In the present study, we report that acyl-homoserine lactones (AHL), the essential signaling molecules of quorum sensing in many gram-negative bacteria, can trigger phage production in soil and groundwater bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 63 publications
5
98
2
Order By: Relevance
“…Second, we compared the rates of spontaneous phage lysis of ɸ4 lysogens constructed in both the PAO1 and PAO1ΔlasR backgrounds: there was no significant difference in production of free phages in stationary phase cultures (median free phage density: PAO1, 3.4 × 10 8 pfu/mL, PAO1ΔlasR, 3.3 × 10 8 pfu/mL; Mann-Whitney test; W = 92.0, P = 0.345). Thus, although direct interaction between temperate phages and bacterial QS has been reported in other systems, via QS induced lysis by phages (39) or QS mediated alteration of phage receptor expression by bacteria (40), this does not appear to be an important factor in our study. Phages may have simply increased the supply of large effect mutations available to natural selection, notably via ɸ4 prophage integrations into mvfR (Fig.…”
Section: Resultscontrasting
confidence: 37%
“…Second, we compared the rates of spontaneous phage lysis of ɸ4 lysogens constructed in both the PAO1 and PAO1ΔlasR backgrounds: there was no significant difference in production of free phages in stationary phase cultures (median free phage density: PAO1, 3.4 × 10 8 pfu/mL, PAO1ΔlasR, 3.3 × 10 8 pfu/mL; Mann-Whitney test; W = 92.0, P = 0.345). Thus, although direct interaction between temperate phages and bacterial QS has been reported in other systems, via QS induced lysis by phages (39) or QS mediated alteration of phage receptor expression by bacteria (40), this does not appear to be an important factor in our study. Phages may have simply increased the supply of large effect mutations available to natural selection, notably via ɸ4 prophage integrations into mvfR (Fig.…”
Section: Resultscontrasting
confidence: 37%
“…In contrast, several well-characterized conditions, such as mitomycin C treatment, use of antibiotics, UV light, and physiological stresses (e.g., amino acid deprivation), are known to promote mobilization of prophage accessory elements. Additionally, it was recently demonstrated that phage production by P. aeruginosa in soil and groundwater can be triggered by acyl-homoserine lactone quorum-sensing signal molecules (73). Thus, phage-mediated HGT may occur in a microbial population density-dependent manner, consistent with the prevailing thought that high bacterial density niches such as biofilms are rich environments for HGT (202).…”
Section: Hgt and Evolution Of The Accessory Genomementioning
confidence: 52%
“…Multiple infections in temperate phages have received some attention and the fitness consequences for individual phages have been addressed (Boyd and Bidwell, 1962;Serra-Moreno et al, 2008), but never in the context of prophage induction. Recently, it has been shown that prophage induction can occur in response to changes in bacterial density and it has been proposed that it is more than an adaptation to escape from a cell bound to die (Ghosh et al, 2009). The ability of prophages to respond to changes in transmission opportunities emphasizes The results herein emphasize the importance of multiple infections for natural phage populations, as they clearly show that lytic productivity of prophages declines, often substantially, when a host is shared between phages.…”
Section: Patterns Of Competitive Interactions Among Lambdoid Phagesmentioning
confidence: 56%
“…This changes once host DNA has been damaged. The bacterial stress response and possibly other signals can trigger the induction of the prophage, which then enters lytic development and finally lyses the host cell (Ptashne, 2004;Shkilnyj and Koudelka, 2007;Ghosh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%